PENERAPAN RESTORATIVE JUSTICE TERHADAP PENYELESAIAN PERKARA KECELAKAAN LALU LINTAS - Sukahar, Onkoseno Grandiarso (Jurnal Idea Hukum, 2023)
Traffic problems are one of the problems that often occur in developed and developing countries. So far, the resolution of traffic accident cases is mostly resolved by penal efforts compared to non-penal efforts. Based on this, the author wants to analyze and understand the expansion of the application of the concept of restorative justice in solving traffic accident cases and the legal consequences for perpetrators by applying the concept of Restorative Justice in traffic accident cases. This study uses a descriptive analysis method with a normative juridical approach. The results of this study indicate that the concept of applying restorative justice in solving traffic accident cases is the goal of punishment because imprisonment is not the best solution in solving traffic accident cases, because the losses caused to victims can still be restored so that the spirit to seek recovery at once ensure the creation of a sense of justice and humanity, prioritizing the interests of victims and perpetrators. And the legal consequences for the perpetrators are the obligation to return, replace or restore all losses caused by traffic accidents caused by the perpetrators so that justice can be achieved for the victims.